Cross Sectional Study on Information System Facilities on End-User Satisfaction: Study at Retail in Bandung - Iwan Sidharta; Rahmahwati Rahmahwati (P3M, STIE Pasundan, Bandung, Indonesia., 2023)
This study explores the impact of information system facilities on end-user satisfaction in the retail sector in Bandung. The researchers adopted a survey approach and collected data from 93 employees working in the retail sector—the research instrument was distributed through a Google Form. The study's prediction model used structural equation modeling (SEM-PLS), and the results of validity and reliability tests of the research constructs met the criteria for validity and reliability.The prediction results reveal that information system facilities significantly influence the perceived ease of use and usefulness. However, they have a different impact on end-user satisfaction. The study's implications indicate that the ease of use of the information system plays a crucial role. When the system is easy to use, with an intuitive user interface and clear operational procedures, employees will be satisfied with operating the system. However, satisfaction is limited to ease of use and is not directly linked to the perceived benefits of employees.